Endovascular Management of Hepatic Encephalopathy - Hieu Le; Siddhant Thukral; A. Michael Devane; Souheil Saddekni; Rakesh K. Varma (Journal of Clinical Interventional Radiology ISVIR)
Transjugular intrahepatic portosystemic shunt (TIPS) and spontaneous portosystemic shunts (SPSS) may lead to new or worsening hepatic encephalopathy (HE), especially in patients with chronic liver disease. Patients with medically refractory HE (rHE) may benefit from endovascular interventions. In this review, we briefly describe the post-TIPS and SPSS vascular anatomy, pathophysiology, classification, factors associated with HE, and the medical management of HE. In addition, we will discuss current endovascular techniques for HE management, their advantages, disadvantages, and review of the current literature.